Moderasi Orientasi Kewirausahaan pada Pengaruh Stres dan Beban Kerja terhadap Kinerja UMKM Multi-Peran - Sari, Juwita; Laily, Nur; Jayanti, Risma Dwi (Jurnal Samudra Ekonomi dan Bisnis, 2026)
This study aims to examine how job stress and workload affect the performance of micro, small, and medium enterprise (MSME) owners who perform multiple roles simultaneously, and to analyze the role of entrepreneurial orientation as a moderating variable in this relationship. The study used a survey method of 114 multi-role MSME owners in Surabaya City. Data were collected through a structured questionnaire and analyzed using the PLS-SEM method. The analysis results indicate that job stress and workload negatively influence the performance of MSME owners. In addition, entrepreneurial orientation has been proven to be able to reduce the negative impact of job stress and workload on business performance. These findings indicate that entrepreneurial orientation plays a role as a personal resource that helps entrepreneurs manage work demands more adaptively. This study provides a theoretical contribution to the development of entrepreneurship studies based on the Job Demands–Resources framework.